2015
DOI: 10.1177/0284185114520862
|View full text |Cite
|
Sign up to set email alerts
|

Role of diffusion-weighted MRI in acute pyelonephritis: a prospective study

Abstract: ADC values derived from the diffusion sequence have significantly lower values in renal abscesses than in areas of nephritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
23
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 13 publications
(20 reference statements)
2
23
0
1
Order By: Relevance
“…Our results showed that the 46 inflammatory foci had statistically lower ADC values (1.43 ± 0.32 9 10 -3 mm 2 /s) than healthy parenchyma, as measured in the 22 patients with suspected APN (2.06 ± 0.16 9 10 -3 mm 2 /s) and in the 26 patients without suspected APN (1.99 ± 0.14 9 10 -3 mm 2 /s). The ADC ability to identify APN foci in transplanted kidneys, as estimated by the ROC curve, was excellent (95% CI for AUC 0.995-1), determining ADC < 1.9 9 10 -3 mm 2 /s as the region typical of APN foci (PPV = 94% and NPV = 100%) The role of diagnostic imaging in confirming a clinical suspicion of APN and its impact on treatment decisions has been reported by several studies [14][15][16][17][18][19]. In particular it was also emphasized that imaging is indispensable for confirming treatment effectiveness during follow-up [20].…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Our results showed that the 46 inflammatory foci had statistically lower ADC values (1.43 ± 0.32 9 10 -3 mm 2 /s) than healthy parenchyma, as measured in the 22 patients with suspected APN (2.06 ± 0.16 9 10 -3 mm 2 /s) and in the 26 patients without suspected APN (1.99 ± 0.14 9 10 -3 mm 2 /s). The ADC ability to identify APN foci in transplanted kidneys, as estimated by the ROC curve, was excellent (95% CI for AUC 0.995-1), determining ADC < 1.9 9 10 -3 mm 2 /s as the region typical of APN foci (PPV = 94% and NPV = 100%) The role of diagnostic imaging in confirming a clinical suspicion of APN and its impact on treatment decisions has been reported by several studies [14][15][16][17][18][19]. In particular it was also emphasized that imaging is indispensable for confirming treatment effectiveness during follow-up [20].…”
Section: Discussionmentioning
confidence: 92%
“…In particular it was also emphasized that imaging is indispensable for confirming treatment effectiveness during follow-up [20]. DW-MRI with ADC allows functional evaluation of renal lesions and was proved to be reliable for diagnosing APN in native kidneys by several authors [14][15][16][17]. On the contrary, there are still relatively few studies in the literature on the use of DWI in transplanted kidneys, even if the initial results on its use for the assessment of early graft deterioration encountered in nearly 30% of renal allografts seem encouraging [21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A limitation of diffusion is a common finding for brain abscesses and indicates a high cellular content and hyperviscosity (7). Rathod et al (8) stressed the role of DWI without contrast in the diagnosis of renal abscesses. The differential diagnosis of renal aspergilloma includes primary and secondary renal malignancies (particularly RCC), lymphoma, bacterial pyelonephritic abscess, renal tuberculosis, and infarction with central necrosis (6).…”
Section: Discussionmentioning
confidence: 99%
“…El cintigrama renal DMSA ha sido considerada la técnica de referencia para demostrar pielonefritis aguda (PNA), pero de acuerdo a las guías internacionales actuales no se recomienda su uso rutinario 1,2 . Varios estudios han mostrado la utilidad de la resonancia magnética (RM) en niños con PNA y en los últimos años algunas publicaciones han demostrado que las secuencias de difusión (DWI) son comparables a las secuencias standard contrastadas con gadolinio en la capacidad de identificar compromiso parenquimatoso renal en niños con sospecha de PNA 3,4,5,6 . …”
unclassified